ANALISIS KRISIS SAMPAH PLASTIK TERHADAP EKOSISTEM PESISIR MELALUI EKONOMI SIRKULAR SEBAGAI SOLUSI DI TANJUNG BAYANG KOTA MAKASSAR - Nur Rahmayani Ade Putri; Rusdi; Ibrahim (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine: 1) What is the picture of plastic waste in Tanjung Bayang, Makassar City. 2) How does the plastic waste crisis impact the coastal ecosystem in Tanjung Bayang, Makassar city. 3) How a circular economy approach can address the plastic waste crisis. The research used was a qualitative case study approach. Data collection was conducted through observation, interviews, and documentation. The results of the study show that: 1) The Tanjung Bayang Coast still faces the problem of scattered garbage due to human activity and is also exacerbated by the rainy season. In addition, local communities have implemented a waste management system through waste banks and waste recycling efforts, or landfilling waste. 2) The impact of the waste crisis on coastal ecosystems and the presence of waste that impacts marine habitats, if the waste is cleaned up immediately, the possibility of disruption to marine habitats can be minimized. And it also has an impact on the economy of coastal communities due to the lack of visitors due to unclean beaches. And 3) A circular economy can overcome plastic waste through waste management with two methods, namely waste banks and recycling, where previously the waste management method with this method had been running with the help of the Community, Students, and LPM (Community Empowerment Institution).